Pengaruh Model Pembelajaran Visual Auditori Kinestetik (VAK) melalui Strategi Pembelajaran Aktif Berbantuan Diorama terhadap Pemahaman Konsep IPAS Siswa Kelas IV SDN 01 Gedung Ketapang Lampung Utara - Citra Muhara Billa; Siti Zulaikhah; Yuli Yanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Understanding science concepts is defined as the skills students need to understand, connect, and apply concepts in everyday life. However, based on the results of a pre-study conducted on fourth-grade students at SDN 01 Gedung Ketapang, it is still relatively low. Therefore, a learning model that can engage students actively and improve their conceptual understanding is needed. The purpose of this study was to determine whether the Visual Auditory Kinesthetic (VAK) learning model through an active learning strategy assisted by dioramas has an effect on the conceptual understanding of fourth-grade students at SDN 01 Gedung Ketapang, North Lampung. The research method used in this study was quantitative and a quasi-experimental research design. Class IVA was used in this study as the experimental class, receiving the VAK model with dioramas as the medium, and the control class, receiving the SAVI model, which was used for class IVB. Pretest and posttest results were collected as research data, and analysis was conducted using descriptive statistics, normality tests, homogeneity tests, and independent sample t-tests using SPSS. The average result of the posttest score of the experimental class was 83.5, while the experimental class obtained an average score of 56.5, lower than the experimental class. In the hypothesis testing, the Sig value was 0.000 (<0.05), so it can be said that H0 was rejected and H1 was accepted, which means that the Visual Auditory Kinesthetic (VAK) learning model through active learning strategies assisted by dioramas has a significant influence on and is effective in improving students' understanding of science concepts.